ANALISIS ALIH KODE SERTA CAMPUR KODE YANG DITEMUKAN PADA LIRIK LAGU DARI BOY GRUP NCT 127 - Amilandasari Amilandasari (Universitas Diponegoro, 2023)
The purpose of this research is to identify code switching and code mixing used in the song lyrics of the boy group NCT 127, as well as the form of the code, as well as to conduct further analysis of the song. Chain and Long Slow Distance are the songs used in this research. In this study, the authors used a descriptive method of code switching and code mixing discussed through sociolinguistics. In his study, the authors started the research by first gathering information by listening to the involvement advanced free of convensation (SBLC) namely searching for song lyrics, listening to song, listening, and writing down song lyrics. Afther that, the information will be described using the intralingual equivalent method to ensure that the data are selected according to their respective classifications. Next, the writer will investigate the reasons for code switching and code mixing in song lyrics, as well as looking for words in Japanese. The results of the research showed that there was external code switching in the form of intrasentential and also intersentential, but there was no internal code switching found in the 2 songs. In code mixing, only code mixing was found but it has various forms, namely in the form of words, clauses, phrases, and also repetition of words. The cause of code switching and code mixing is to emphasize the spoken sentence and as a form of casualness (informal situations) and also the intentional element of the speaker. The total data found is 22 data. <a href=